Kriging modeling of vertical behavior of environmental noise through thematic maps during cultural festivities in Puno and Juliaca, Perú - Marin-Mamani, Grover (2021)
Noise pollution affects the quality of life of people all over the world. The origin can be due to various causes including cultural activities. The objective was to model the vertical distribution on thematic maps using the Kriging technique in the parade of the Virgin of Candelaria in Puno and the parade of the Juliaca carnival in Peru. The measurements were made using the road and grid methods, with four indicators (Lmin, Lmax, LApk and LAeq). Twenty-eight samples were used with a total of 112 monitoring points, which were modeled by height at a ratio of every 5 meters. The values at the 5, 20, 50 and 100 meter elevations were mathematically calculated to see the altimetric behavior of the dB(A), as a control to use the data with the sound level meter at these altitudes, which are georeferenced in 19 L UTM WGS 84, for which he used a CASELLA CEL 6X0 Sound Level Meter. In both cities it was obtained that the noise is attenuated when the altitude increases, being the values for the altitudes +5 m and +20 m, in both cases above the permissible values of LAeq, according to the Supreme Decree Nº 085-2003-PCM (minimum 50 dB and maximum 60 dB). No statistically significant differences in the noise levels were evident for both cities with 95% confidence in each of the measured indicators.